SAT0554 Assessing SUA, Flare Rates, and Tophi in Patients with Gout Treated Xanthine Oxidase Inhibitors in the United States. (23rd January 2014) - Khanna, P. P.; Baumgartner, S.; Khanna, D.; Storgard, C.; Morlock, R.
Abstract : Background: Gout is a common inflammatory arthritis and its worldwide prevalence is increasing. Serum urate (sUA) levels, tophi and flares have been associated with increasing disease burden among patients with gout. Objectives: In a cohort of patients treated with xanthine oxidase (XO) inhibitors assess the relationship between sUA, flares, tophi, treatment duration and identify characteristics of patients with high levels of disease activity and impairment (patients with sUA > 6, multiple flares and tophi) despite active treatment. Methods: Data were assessed from a quantitative survey of US physicians. Laboratory and clinical data were confirmed through chart audits using a structured case report form created by Bio-Trends. The sample was restricted to patients treated with XO inhibitor urate lowering therapy (ULT). Physician type (rheumatologist vs. primary care physician [PCP]), patient socio-demographics factors, flare rates (treatment and non-treatment related), treatment duration and time since initial diagnosis were recorded. Descriptive statistics were used to describe the relationship between sUA, flares, tophi, treatment duration and identify characteristics of patients with sUA > 6, multiple flares (2+) flares and tophi. Comorbidities were captured using chart review and analyzed as present or absent. A multivariate model was used to assess the impact of patient, clinician, and treatment variables on patients with dependent variable being patients who had sUA > 6, multiple flares, and tophi. Results: The sample included 125 rheumatologists and 124 PCPs. Of the 1, 245 patients with gout, 858 (69%) were treated with a XO inhibitor: 621 (72.4%) were treated with allopurinol and 237 (27.6%) were treated with febuxostat. Average sUA was positively correlated with tophi (r=0.18; p<0.01) and number of flares (r=0.29; p<0.01). 131 (15%) patients were classified as difficult to treat having a sUA > 6, multiple flares and tophi. These patients were more likely to be treated by a rheumatologist (69%) and had more comorbid conditions. A multivariate model controlling for patient and clinical covariates identified being treated by a rheumatologist (OR 1.62; p=0.03), use of febuxostat (OR 1.63; p=0.03), comorbid alcoholism (OR 2.62; p<0.01), chronic kidney disease (CKD) (OR 3.13; p<0.01), congestive heart failure (CHF) (OR 3.66; p<0.01), and hypertension (odds ratio 1.99; p<0.01)to be predictive of sUA > 6, multiple flares and tophi. For patients treated with allopurinol the average daily dose was approximately 300 mg per day and there was no difference in dosing by sUA level (p=0.9). Image/graph: Conclusions: In patients with gout, sUA levels were positively correlated with number of flares experienced in a 12 month period and the presence of tophi and negatively correlated with time on treatment. Patients with sUA > 6, multiple flares, and tophi were more likely to have comorbidities that limit treatment options. Disclosure of Interest: P. Khanna Speakers bureau: Takeda, S. Baumgartner Employee of: Ardea Biosciences, D. Khanna Consultant for: Savient, Takeda and Ardea Biosciences, Speakers bureau: Savient, C. Storgard Employee of: Ardea Biosciences, R. Morlock Employee of: Ardea Biosciences